Hepatitis C Virus Infection in Pregnant Individuals with Opioid Use Disorder and Its Association with Preterm Birth - Cheedalla, Aneesha; Berry, Marissa; Abdelwahab, Mahmoud; Cowen, Jamie; Stiles, Alexandra; Mason, Isabelle; Honegger, Jonathan R.; Rood, Kara M. (American Journal of Perinatology, 2024)
Both hepatitis C virus (HCV) and opioid use disorder (OUD) have been associated with higher rates of preterm birth (PTB). It is unknown whether the higher prevalence of HCV in individuals with OUD may contribute to this association. The objective of this study is to evaluate the association between HCV and PTB in pregnant individuals with OUD.We conducted a retrospective cohort of pregnant individuals with OUD who participated in more than three visits in a co-located multidisciplinary program. Inclusion criteria were a diagnosis of OUD, participation in treatment/prenatal care program, and laboratory evaluation of HCV status. The primary exposure was the presence of HCV antibodies, and secondarily, a detectable viral load (viremia). The primary outcome was PTB, which was further classified as spontaneous or iatrogenic. Multivariable logistic regression was used to detect associations while adjusting for race, history of prior PTB, and tobacco use.A total of 941 individuals were included in the study, 404 with HCV and 537 without. Rates of PTB did not differ between those with compared to those without HCV (20.3 vs. 23.8%, adjusted odds ratio [aOR] = 0.75 [95% confidence interval (CI): 0.53–1.07]). There were similar rates of spontaneous PTB (13.1 vs. 16.2%, aOR = 0.79 [95% CI: 0.43–1.45]) and iatrogenic PTB (7.2 vs. 7.6%, aOR = 1.26 [95% CI: 0.69–2.30]). Comparing those with viremia to those without, there were also similar rates of overall PTB (21.6 vs. 17.9%, aOR = 0.86 [95% CI: 0.52–1.44]), spontaneous PTB (13.3 vs. 12.9%, aOR = 0.97 [95% CI: 0.52–1.87]), and iatrogenic PTB (8.3 vs. 5.0%, aOR = 1.83 [95% CI: 0.76–4.94]).HCV does not appear to be associated with spontaneous or iatrogenic PTB in pregnant persons with OUD who are engaged in treatment and prenatal care. The role of co-located multidisciplinary prenatal and addiction programs in the association between HCV and PTB warrants further investigation.
Keywords: hepatitis C virus; opioid use disorder; preterm birth